North-South Displacement Effects of Environmental Regulation: The Case of Battery Recycling - Shinsuke Tanaka; Kensuke Teshima; Eric Verhoogen (Institute of Labor Economics (IZA), 2021)
This study examines the effect of a tightening of the U.S. air-quality standard for lead in 2009 on the relocation of battery recycling to Mexico and on infant health in Mexico. In the U.S., airborne lead dropped sharply near affected plants, most of which were battery-recycling plants. Exports of used batteries to Mexico rose markedly. In Mexico, production increased at battery-recycling plants, relative to comparable industries, and birth outcomes deteriorated within two miles of those plants, relative to areas slightly farther away. The case provides a salient example of a pollution-haven effect between a developed and a developing country.
Keywords: F18; Q56; O15; 330; pollution-haven hypothesis; environmental regulation; infant health